2022
DOI: 10.7324/jabb.2022.100210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic fertilization on productivity of some newly introduced basil varieties under Siwa Oasis conditions

Abstract: A split-plot design field trial was carried out on Ocimum basilicum L. plants at Siwa Oasis, Egypt, during the 2018 and 2019 seasons to study the effect of organic fertilization, cultivation of some foreign varieties, and their combination on yield. The main plots included applying two compost manure levels before planting (24 and 48 m 3 /hectare). Subplots included cultivating five basil varieties (local and four foreign varieties: lime basil, smuglyanka basil, purple basil, and purple ruffles basil). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While the lowest values of these treatment scored by between planting distances (20*20 cm) and F1 in the two cuts and in both seasons. Also, the abovementioned results are met with those attained by, (Khater et al 2020) on Pelargonium Graveolens, found that with aloe extract produced the highest oil yield and oil percentage, Abdel-Mola et al (2022) on Carum Carvi, parameters on oil yield was augmented due to the high dose with aqueous LRE, Toaima et al (2022) on Ocimum basilicum L. Hassan (2023) on Carum carvi, licorice extract gave the highest, ratio of carvone, and limonene.…”
Section: Chlorophyll a B And Carotenoid's Contentsmentioning
confidence: 83%
“…While the lowest values of these treatment scored by between planting distances (20*20 cm) and F1 in the two cuts and in both seasons. Also, the abovementioned results are met with those attained by, (Khater et al 2020) on Pelargonium Graveolens, found that with aloe extract produced the highest oil yield and oil percentage, Abdel-Mola et al (2022) on Carum Carvi, parameters on oil yield was augmented due to the high dose with aqueous LRE, Toaima et al (2022) on Ocimum basilicum L. Hassan (2023) on Carum carvi, licorice extract gave the highest, ratio of carvone, and limonene.…”
Section: Chlorophyll a B And Carotenoid's Contentsmentioning
confidence: 83%
“…e highest yield was achieved by plants receiving mineral fertilizers, which are characterized by the fastest rate of nutrient release into the soil solution. Investigations conducted by Toaima et al (2022) have proved the beneficial effect of composted manure on the yield of various basil varieties. e yield-enhancing effect of organic fertilization on basil field cultivation may be associated with the role of the fertilizer in alleviation of plant stress.…”
Section: Discussionmentioning
confidence: 99%
“…Both the increasing dose of the natural fertilizer and the fertilizer type had an effect on the amount of the essential oil components in the basil herb. Toaima et al (2022) used composted manure to fertilize basil at a dose of 24 m 3 ha and found that 1,8-cineole (56.86%), l-linalool (11.13%), and cinnamic acid methyl ester (8.45%) were the main compounds in local basil from the second harvest. In turn, aer treatment with a higher manure dose (48 m 3 ha), the following concentrations of the main components of basil oil were determined: 1,8-cineole (46.47%), cinnamic acid methyl ester (22.53%), and l-linalool (10.04%).…”
Section: Discussionmentioning
confidence: 99%
“…The gap in the study is the need for more information on producing a decent rosemary yield in this area. The cultivation of rosemary has just been made available to the local farmers there (El-Mahrouk et al, 2018;Hanafy et al, 2022;Toaima et al, 2022;Volza's Global Export Data).…”
Section: Introductionmentioning
confidence: 99%